RIGHT CEREBRAL HEMISPHERE PERFORMANCE CONDITIONED BY THE DEGREE OF IMAGEABILITY OF WORDS IN A LEXICAL DECISION EXPERIMENT WITH SEMANTIC PRIMING - Monsalve González, Asunción (Anales de Psicología / Annals of Psychology, 2001)
The object of this study is to look more deeply into the interaction between the visual field of presentation of stimuli, and the variables imageability and frequency of words found in previous studies. To do this we have, in this case, designed a lexical decision task with semantic priming. The results obtained suggest that left hemisphere superiority is seen on processing abstract linguistic material and pseudowords. This superiority, however, disappears when the material to be processed has a high degree of imageability or concreteness. The results, however, seem to indicate that right hemisphere performance appears to be affected more by the factor of imageability than that of frequency, coinciding with a large part of existing research and supporting the probable bilateral representation of concrete words.